Thymus zygis subsp. zygis an Endemic Portuguese Plant: Phytochemical Profiling, Antioxidant, Anti-Proliferative and Anti-Inflammatory Activities - Amélia M. Silva; Carlos Martins-Gomes; Eliana B. Souto; Judith Schäfer; João A. Santos; Mirko Bunzel; Fernando M. Nunes (MDPI AG, 2020)
Thymus zygis subsp. zygis is an endemic Portuguese plant belonging to the Thymus zygis species. Although T. zygis is commonly used as a condiment and as a medicinal herb, a detailed description of the polyphenol composition of hydroethanolic (HE) and aqueous decoction (AD) extracts is not available. In this work, we describe for the first time a detailed phenolic composition of Thymus zygis subsp. zygis HE and AD extracts, together with their antioxidant, anti-proliferative and anti-inflammatory activities. Unlike other Thymus species, T. zygis subsp. zygis extracts contain higher amounts of luteolin-(?)-O-hexoside. However, the major phenolic compound is rosmarinic acid, and high amounts of salvianolic acids K and I were also detected. T. zygis subsp. zygis extracts exhibited significant scavenging activity of ABTS+, hydroxyl (•OH), and nitric oxide (NO) radicals. Regarding the anti-proliferative/cytotoxic effect, tested against Caco-2 and HepG2 cells, the AD extract only slightly reduced cell viability at higher concentrations (IC50 > 600 µg/mL, 48 h exposure), denoting very low toxicity, while the HE extract showed a high anti-proliferative effect, especially at 48 h exposure (IC50 of 85.01 ± 15.10 μg/mL and 82.19 ± 2.46 μg/mL, for Caco-2 and HepG2, respectively). At non-cytotoxic concentrations, both extracts reduced the nitric oxide (NO) release by lipopolysaccharide (LPS)-stimulated RAW 264.7 cells (at 50 μg/mL, HE and AD extracts inhibited NO release in ~89% and 48%, respectively). In conclusion, the results highlight the non-toxic effect of aqueous extracts, both resembling the consumption of antioxidants in foodstuff or in functional food. Furthermore, the HE extract of T. zygis subsp. zygis is a source of promising molecules with antioxidant, anti-inflammatory and anticancer activities, highlighting its potential as a source of bioactive ingredients for nutraceutical and pharmaceutical industries.